Quantile stable mechanisms - Peter Chen; Michael Egesdal; Marek Pycia; M. Bumin Yenmez (Games, 2021)
We introduce a new class of matching mechanisms - quantile stable mechanisms - that generate stable matchings that can be seen as a compromise between sides of a two-sided market. We show that responsiveness is a sufficient condition for the existence of such mechanisms and that all such mechanisms are distinct. We also analyze the manipulability of these mechanisms by market participants.
Keywords: 330; auctions; contracts; incentives; matching; mechanisms